Central Nervous System Lymphoma in a 3-Year-Old Male Suffering from a Severe Juvenile Xanthogranuloma – the Usefulness of Perfusion Weighted Imaging and Diffusion Weighted Imaging in the Diagnostics of Pediatric Brain Tumors - Neska-Matuszewska, Małgorzata (Pol J Radiol, 2015)
BACKGROUND: Primary Central Nervous System Lymphomas (PCNSLs) are rare, malignant brain tumors derived from lymphocytes B. Juvenile xanthogranuloma (JXG) is a non-Langerhans histiocytic cell disorder in children which mostly affects the skin. Rare fatalities have been reported in extracutaneous manifestation. Brain magnetic resonance imaging (MRI) is a method of choice in the diagnostics of all neoplastic CNS lesions. Perfusion weighted imaging (PWI) and diffusion weighted imaging (DWI) allow for more detailed analysis of brain tumors including the rate of neoangiogenesis and cellularity. We presented a pediatric patient suffering from JXG with CNS involvement and the role of brain MRI including DWI and PWI in the evaluation of brain focal lesions. CASE REPORT: A 3-year-old male with severe JXG underwent two stem cell transplantations with a development of neurological complications. The patient underwent emergency CT and MRI which revealed a non-specific enhancing focal brain lesion. In DWI it showed restricted diffusion while PWI revealed low values of rCBV and the signal intensity curve returning above the baseline level. Advanced MRI techniques such as DWI and PWI suggested PCNSL. Stereotactic biopsy confirmed PCNSL due to Ebstein-Barr virus reactivation. CONCLUSIONS: The use of advanced MRI sequences is important to differentiate brain lesions in pediatric patients. The use of PWI and DWI facilitated the diagnosis of PCNSL. It is important to remember that PCNSLs show a very typical pattern of changes visualized with MRI such as: usually strong homogenous enhancement, restricted diffusion and low perfusion.